Storytelling Technique for Peer Group Communication about Reproductive Health on “Bacarita Kespro” - Meok, Irene Aprilya; Abrar, Ana Nadhya (UI Scholars Hub, 2025)
This study examines storytelling techniques for adolescents in group communication as a medium for reproductive health education in the “Bacarita Kespro”, a program organized by Tenggara Youth Community. The use of new educational methods is essential as traditional lecture-based approaches have proven ineffective in educating adolescents about reproductive health. Guided by narrative communication theory and symbolic convergence theory, this study employs a qualitative approach combining observation and interview data. The results show that storytelling practices in group communication involve adolescents alternating roles as storytellers and listeners, focusing on the theme of changes during puberty. From the perspective of narrative understanding, the stories are of high quality—culturally relevant, logical, and grounded in real-life experiences directly shared by adolescents. Furthermore, visual aids play an important role in helping participants both tell and comprehend the story. These findings provide new insights into the health communication sector about how adolescents communicate in the context of reproductive health, highlighting the importance of their active participation in the learning process.